Dual-energy snap-shot perfusion CT in suspect pulmonary nodules and masses and for lung cancer staging - Janssen, Sonja; Henzler, Claudia; Weis, Meike; Schönberg, Stefan; Apfaltrer, Paul (European journal of radiology, 2015)
Dual energy computed tomography (DECT) has proven its clinical usefulness for improved tissue characterization within the past years. In thoracic oncology, DECT can be used to differentiate between benign and malignant pulmonary nodules and masses. In patients with known lung cancer, DECT can add incremental functional information to staging scans, therapeutic response evaluation, as well as to the assessment of lung function. This review aims to give an overview on the current clinical utilities of DECT of the chest, its multiple post-processing applications and dose saving options. Furthermore, this review highlights promising applications of DECT that merit implementation in future clinical routine.